Comparison of fermentation kinetics (in vitro) of grass and shrub legume leaves: The pattern of gas production, organic matter degradation, pH and NH3 production - Widiawati, Y; Thalib, A (Indonesian Animal Sciences Society, 2006)
Rumen microbes convert carbohydrate in a feed to useful product such as VFA, microbial protein and B-vitamin; and some waste products such as CH4 and CO2. The amount and pattern of each product depend on the type of feed Sonsumed by the animal. High fiber diet produce high gas and VFA, while high protein diet produce high NH3. Two types of feeds, grass and legume, have different cell structure and content, thus might have different pattern of rumen fermentation and product. In vitro method developed by Theodorou and Brooks was used to determine the pattern of rumen fermentation and product of two types of feeds, namely grass and legume. Result shows that legume has higher amount of OM degraded and produce higher amount of NH3 compared to grass. On the basis of OM degraded, the grass yielded higher volume of gas than that of legume. The two types of feeds did not change the pH of rumen fluid. Key Words: Grass, Shrub Legume, Gas And Ammonia Production, Organic Matter Digestibility